IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) MENGGUNAKAN MEDIA PAPAN TEKA TEKI SILANG PADA PEMBELAJARAN IPAS KELAS V DI SEKOLAH DASAR NEGERI ALASOMBO 02 KECAMATAN WERU KABUPATEN SUKOHARJO - Rizka Rijaya; Moefty Mahendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the cooperative learning model Teams Games Tournament (TGT) using crossword puzzle media (TTS) in the IPAS (Integrated Natural Science and Social Studies) lessons for fifth-grade students at SD Negeri Alasombo 02. The research used a qualitative approach with a phenomenological design. Data were collected through observation, interviews, and documentation involving both teachers and students. The findings indicate that the TGT model with TTS media successfully created an active and engaging learning environment. The lesson began with a conducive opening, followed by material delivery using interesting PowerPoint slides, and ended with a TGT crossword puzzle tournament. This approach successfully enhanced student engagement in actively and collaboratively understanding the material. Although there were some challenges, such as limited time and technical issues with the projector, overall, this model encouraged students to actively participate, improved their understanding of the material, and developed their social skills and enthusiasm for learning. The provision of rewards further strengthened student motivation. The TGT model with TTS proved effective in creating meaningful and enjoyable learning experiences.